Modulation of Innate Antiviral Immune Response by Porcine Enteric Coronavirus - Zhang, Kunli; Lin, Sen; Li, Jianhao; Deng, Shoulong; Zhang, Jianfeng; Wang, Sutian (Frontiers in Microbiology, 2022)
Host’s innate immunity is the front-line defense against viral infections, but some viruses have evolved multiple strategies for evasion of antiviral innate immunity. The porcine enteric coronaviruses (PECs) consist of porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), transmissible gastroenteritis coronavirus (TGEV), and swine acute diarrhea syndrome-coronavirus (SADS-CoV), which cause lethal diarrhea in neonatal pigs and threaten the swine industry worldwide. PECs interact with host cells to inhibit and evade innate antiviral immune responses like other coronaviruses. Moreover, the immune escape of porcine enteric coronaviruses is the key pathogenic mechanism causing infection. Here, we review the most recent advances in the interactions between viral and host’s factors, focusing on the mechanisms by which viral components antagonize interferon (IFN)-mediated innate antiviral immune responses, trying to shed light on new targets and strategies effective for controlling and eliminating porcine enteric coronaviruses.